Functionalization of fullerene at room temperature: toward new carbon vectors with improved physicochemical properties. Issue 114 (29th November 2016) - Beiranvand, Z.; Kakanejadifard, A.; Donskyi, I. S.; Faghani, A.; Tu, Z.; Lippitz, A.; Sasanpour, P.; Maschietto, F.; Paulus, B.; Unger, W. E. S.; Haag, R.; Adeli, M.
Abstract : In this work, fullerene has been functionalized with cyanuric chloride at room temperature by a nitrene mediated [2 + 1] cycloaddition reaction. Abstract : In this work, fullerene has been functionalized with cyanuric chloride at room temperature by a nitrene mediated [2 + 1] cycloaddition reaction. The adduct after functionalization is inherently in the form of azafulleroid and shows broad UV absorption in the wavelength range of 200–800 nm, as well as photothermal conversion and fluorescence with a high quantum yield.